The perception of Malaysian youth towards Indonesian modest fashion / Husna Saaidin ... [et al.] - Saaidin, Husna; Saidan, Suriati; Wan Kamarulbaharin, Wan Nadhra Ixora; Abu Bakar, Shaheela (Universiti Teknologi MARA, Perak, 2022)
The Malaysian modest fashion industry is a lucrative product category that is worth looking out for since 61.3% of its population are Muslims. Thus, it is imperative that the preferences of the Muslims youth in fashion design are determined. This could invariably give fashion designers the direction forward in creativity and productivity. The preferences of modest fashion in this study were determined by comparing modest clothing of well-known designers from Indonesia and Malaysia. The characteristics of modest fashion designs done by selected fashion designers from both countries were observed and various main features were categorized. A quantitative method of surveys was then done to gauge the perceptions of 50 Malaysian youth towards their preferred modest fashion design by comparing the characteristics of Indonesia and Malaysian modest fashion. Further qualitative method was also done by giving the respondents an open question. It was found that the respondents preferred minimalist designs and perceived that Malaysian modest fashion designs are more sharia compliant compared to the Indonesian modest fashion design. Malaysian youth would like to see more creative and innovative designs in the future. It is recommended that Malaysian designers to use a bolder approach and more creativity in their designs. The instrument used could be enhanced by giving more clothing examples that could identify more characteristics of the modest fashion designs that meet consumers demands.